On the Recent Trends in Expansive Soil Stabilization Using Calcium-Based Stabilizer Materials (CSMs): A Comprehensive Review - Fazal E. Jalal; Yongfu Xu; Babak Jamhiri; Shazim Ali Memon (Advances in Materials Science and Engineering)
Calcium-based stabilizer materials (CSMs) exhibit pozzolanic properties which improve the properties of clayey soils by hydration, cation exchange, flocculation, pozzolanic reaction, and carbonation. In this comprehensive review, comprising over past three decades from 1990 to 2019, a mechanistic literature of expansive soil stabilization by incorporating CSMs is presented by reviewing 183 published research articles. The advantages and disadvantages of CSMs as the ground stabilizing agent are succinctly presented, and the major outcomes of physicochemical effects on soil properties are discussed in detail. After blending with CSM, the main and interaction effects on soil properties with focus on chemical processes such as X-ray fluorescence, X-ray diffraction analyses, and microstructure interaction by using scanning electron microscopy and thermogravimetric analysis have been reviewed in light of findings of past researchers. This work will help geotechnical engineers to opt for suitable CSM in the field of geoenvironmental engineering in committing to sustainable construction of civil engineering structures over expansive soils.